2007
DOI: 10.1093/bioinformatics/btl671
|View full text |Cite
|
Sign up to set email alerts
|

BioWeka—extending the Weka framework for bioinformatics

Abstract: The software, documentation and tutorial are available at http://www.bioweka.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 14 publications
0
36
0
Order By: Relevance
“…The results revealed that both algorithms violated some of the necessary properties identified as metamorphic relations indicating faults or unexpected behaviours. Also, some real faults were detected in the open-source machine learning tool Weka [110]. Finally, Jing et al [111] presented a set of metamorphic relations for association rule algorithms and evaluated them using a contact-lenses data set and the Weka tool.…”
Section: Machine Learningmentioning
confidence: 99%
“…The results revealed that both algorithms violated some of the necessary properties identified as metamorphic relations indicating faults or unexpected behaviours. Also, some real faults were detected in the open-source machine learning tool Weka [110]. Finally, Jing et al [111] presented a set of metamorphic relations for association rule algorithms and evaluated them using a contact-lenses data set and the Weka tool.…”
Section: Machine Learningmentioning
confidence: 99%
“…Weka is a user-friendly machine learning software package with a graphical user interface [27]. Weka is widely utilized in biology, bioinformatics, and biochemistry [28]. For each dataset, we ranked five features (state, migration distance (long or short), and maximum, minimum, and mean temperature) according to their association level with changes in the migration pattern at arrival date, departure date, and duration of stay.…”
Section: Feature Selection Analysismentioning
confidence: 99%
“…Weka is a collection of state-of-the-art data mining algorithms and data preprocessing methods for a wide range of tasks such as data preprocessing, attribute selection, clustering, and classification. Weka has been used in prior research both in the field of clinical data mining [34] and in bioinformatics [35].…”
Section: Modelingmentioning
confidence: 99%